The SVZ stem cell niche–components, functions, and in vitro modelling - Eşiyok, Nesil; Heide, Michael (Frontiers in Cell and Developmental Biology, 2023)
Neocortical development depends on the intrinsic ability of neural stem and progenitor cells to proliferate and differentiate to generate the different kinds of neurons in the adult brain. These progenitor cells can be distinguished into apical progenitors, which occupy a stem cell niche in the ventricular zone (VZ), and basal progenitors, which occupy a stem cell niche in the subventricular zone (SVZ). During development, the stem cell niche provided in the SVZ enables the increased proliferation and self-renewal of basal progenitors, which likely underlie the expansion of the human neocortex. However, the components forming the SVZ stem cell niche in the developing neocortex have not yet been fully understood. In this review, we will discuss potential components of the SVZ stem cell niche, i.e. extracellular matrix composition and brain vasculature, and their possible key role in establishing and maintaining this niche during fetal neocortical development. We will also emphasize the potential role of basal progenitor morphology in maintaining their proliferative capacity within the stem cell niche of the SVZ. Finally, we will focus on the use of brain organoids to (i) understand the unique features of basal progenitors, notably basal radial glia; (ii) study components of the SVZ stem cell niche; and (iii) provide future directions on how to improve brain organoids, notably the organoid SVZ, and make them more reliable models human neocortical development and evolution studies.